2000
DOI: 10.1002/1096-908x(200005/06)12:3<143::aid-smr207>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining a legacy: towards support at the architectural level

Abstract: An organization that develops large, software intensive systems with a long lifetime will encounter major changes in the market requirements, the software development environment, including its platform, and the target platform. In order to meet the challenges associated with these changes, software development has to undergo major changes as well. Especially when these systems are successful, and hence become an asset, particular care shall be taken to maintain this legacy; large systems with a long lifetime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…As described in [7], the Jolly Jumper did not reach the same level of quality as the MAB during the development of URSA. During the past four years, the Jolly Jumper was re-implemented from scratch using SDE-specific technology, motivated by its quality, amongst others.…”
Section: Asmentioning
confidence: 87%
See 3 more Smart Citations
“…As described in [7], the Jolly Jumper did not reach the same level of quality as the MAB during the development of URSA. During the past four years, the Jolly Jumper was re-implemented from scratch using SDE-specific technology, motivated by its quality, amongst others.…”
Section: Asmentioning
confidence: 87%
“…In an earlier paper [7], we reported that organizational issues are considerably more demanding than technical issues when developing and subsequently introducing means for AS, i.e., an architectural methodology with an accompanying toolset. In [8], we described influential elements for AS, however, this paper is entirely dedicated to the C-POSH model for embedding AS within organizations.…”
Section: Architectural Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…Enhancements to control flow logic would be expected to be of a deep structure nature because they would most likely involve changes to the semantic component of the system. Furthermore, Bril et al [25] show evidence that good understanding is supported by good documentation.…”
Section: Model Of Information System Changementioning
confidence: 99%